Considerations on the genus Schizachyrium (Poaceae–Andropogoneae) in Central America and West Indies, and confirmation of the occurrence of S. glaziovii - Welker, Cassiano Aimberê Dorneles; Peichoto, Myriam Carolina (Phytotaxa, 2015)
Schizachyrium (Poaceae–Andropogoneae) includes ca. 60 species, 10 of them previously cited for Central America and 13 for West Indies. The confirmation of the occurrence of Schizachyrium glaziovii in these regions is reported here, expanding its northern limit of distribution to Guatemala and Belize. The species was previously accepted only for South America. We provide a description of the species, a distribution map, and a key to distinguish it from S. microstachyum and S. condensatum, species whose circumscriptions are confused in floras of Central America and West Indies. Taxonomic comments, illustrations of the type materials and images of the three species are also provided. A revised synonymy of S. glaziovii is presented and a lectotype for Andropogon condensatus subsp. elongatus (a synonym of Schizachyrium glaziovii) is designated here.